DEVELOPMENT OF DIGITAL MEDIA AND LUDO EKSPONEN TO IMPROVE LEARNING OUTCOMES OF GRADE IX JUNIOR HIGH SCHOOL STUDENTS - Putri Ekawaty Kobandaha; Winda Syam Tonra; Ahmad Choirul Anam (Fakultas Tarbiyah Universitas Ibrahimy, 2022)
This study aims to analyze the use of digital media and Ludo Eksponen which has been developed using the ADDIE model in Team Games Tournament (TGT) type cooperative learning. Furthermore, at the stage of implementation and evaluation of the media, it was seen its effectiveness on mathematics learning outcomes, for junior high school students in class IX on the square number and square root material. The subjects of this study were 30 students at one of The Al-Amien Junior High Schools in Sumenep Regency. The data collection technique used direct observation and giving pretests and pot-tests to research subjects. As a result, there was an increase in the average value between the pretest and post-test results, which was 7.54 and 53.65, respectively. By using a Paired Test sample t-test. Based on the results of the study, it can be concluded that the use of digital media and Ludo Eksponen as manual media in cooperative learning type Team Games Tournament (TGT) was quite effective in improving student learning outcomes on the square number and square root.